Banger Retention Pool As Alternative Control Flood - Yudaningrum, Farida; Ikhwanudin, Ikhwanudin (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2020)
Abstract. Semarang Utara is a lowland where the water level is approximately 2m above sea level so that if the weather is bad, waves or tidal waves occur, sea water will intrude onto the land . This happens almost every day, so a barrier is needed to prevent sea water intrusion into land . Before there was handling then It would be best to create an alternative retention pool simulation in the Banger chatment area . The method used uses primary data and secondary data taken from rainfall data closest to the B anger location, namely BMKG Mariti m. Retention pool simulation results and alternative pump capacities 1 with a pond area of 3.8 ha, input volume 1,199,070 m3 and output volume 432,000 m3, alternative 2 with a pond area of 4.7 ha, input volume 1,198,800 m3 and output volume 432,000 m3, alternative 3 with extensive 5 ha pond, input volume 1,199,070 m3 and output volume 432,000 m3 .Keyword : Pool Retention, Pumps, Channels